Use of a Wearable EEG Headband as a Meditation Device for Women With Newly Diagnosed Breast Cancer: A Randomized Controlled Trial. (September 2019) - Millstine, Denise M.; Bhagra, Anjali; Jenkins, Sarah M.; Croghan, Ivana T.; Stan, Daniela L.; Boughey, Judy C.; Nguyen, Minh-Doan T.; Pruthi, Sandhya
Background: Breast cancer diagnosis and treatment affect quality of life and stress and are associated with fatigue. Meditation interventions are effective strategies for patients with breast cancer but are often limited by poor access, high cost, substantial time commitment, and poor adherence. In this feasibility study, we investigated the use of a portable, wearable, electroencephalographic device for guided meditation practices by breast cancer patients during the period from breast cancer diagnosis until 3 months after surgical treatment.Methods: We enrolled women (age = 20-75 years) who had received a recent diagnosis of breast cancer and planned to undergo surgical treatment. Participants were randomly assigned to perform guided meditation with the device (intervention group) or receive CD-based stress-reduction education (control group). Surveys were used to measure stress, quality of life, and fatigue at baseline, within 4 days before surgery, up to 14 days after surgery, and at 3 months after surgery.Results: In the intervention group, 15 of 17 participants (88.2%) completed the study; in the control group, 13 of 13 participants completed the study (100%). Participants in both groups had less fatigue and stress and improved quality of life at 2 weeks and 3 months after surgery compared with baseline, but there were no significant intergroup differences at any time point.Conclusion: The use of this wearable electroencephalographic device for meditation is a feasible strategy for patients with breast cancer.